Cerebrospinal fluid cytokines in geriatric patients with depressive disorders: A retrospective case-control study - Schou, Morten Brix; Larsen, Jeanette Brun; Stunes, Astrid Kamilla; Sæther, Sverre Georg (Frontiers in Psychiatry, 2022)
Central nervous system inflammation might play a role in patients with depressive disorders. This hypothesis is supported by studies reporting increased cerebrospinal fluid levels of the inflammatory markers interleukin (IL)-6, IL-8 and tumor necrosis factor alpha (TNF-α) in patients with ongoing depression. In this case-control study, we aimed to examine whether these findings also applied to depressed patients in a geriatric population. Cerebrospinal fluid cytokine analyses were performed on 15 patients (age > 60 years) with depressive disorders and 45 age– and sex matched controls (patients with headache or idiopathic facial palsy). IL-6, IL-8, IL-10, TNF-α, monocyte chemoattractant protein-1 and transforming growth factor beta 1 were included in the statistical analyses. Patients with depression had significantly lower cerebrospinal fluid levels of IL-6 as compared to controls (p=0.014) in the univariate analysis. The finding was, however, no longer statistically significant after correction for age and body mass index (p=0.097). Overall, this study indicates that the cytokines included in this study are not significantly altered in geriatric patients with depression. Future studies exploring cerebrospinal fluid cytokine levels should include corrections for possible confounding factors.